Synthesis of π‐Extended Carbazoles via One‐Pot C—C Coupling and Chlorination Promoted by FeCl3. Issue 12 (8th September 2020) - Qian, Yang; Shang, Jia; Lyu, Zhen‐Hua; Huang, Xin; Guan, Ai‐jiao; Xu, Li‐Jin; Gong, Han‐Yuan
Summary of main observation and conclusion: A facile synthesis, functionalization, and emission property of N‐doped carbon‐rich halogenated compound 3, 6, 12, 15‐tetrachloro‐9‐phenyl‐9H‐tetrabenzo[a, c, g, i]carbazole (ClCbz ) was reported. Cost‐effective FeCl3 catalyst serves to break eight C—H bonds of 1, 2, 3, 4, 5‐pentaphenylpyrrole (1 ) and subsequently construct two C—C and four C—Cl bonds in one pot with a high yield of up to 75%. Abstract :